EFEKTIVITAS PELAYANAN PUBLIK DALAM PENGURUSAN KARTU TANDA PENDUDUK DI KANTOR KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG - Adhan, Reski Nursaputri; Jabbar, Abdul; Mustanir, Ahmad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to examine and analyze the effectiveness of public services in the administration of Identity Cards (KTP) at the Baranti Subdistrict Office, Sidenreng Rappang Regency. The research focuses on aspects such as communication, data and document management, information provision, and obstacles faced by officials in implementing population administration services. This study employs a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. Based on the findings, the implementation of public services at the Baranti Subdistrict Office has been relatively effective, as indicated by open communication between officials and the community, as well as a well-structured data management system. However, several obstacles still affect service effectiveness, including limited human resources, inadequate technological facilities, unclear task distribution, and insufficient socialization regarding policy changes. Based on these findings, it is recommended that the subdistrict government improve staff competencies, enhance IT-based service systems, and strengthen internal coordination to ensure that the administration of KTPs can be conducted more quickly, accurately, and transparently.